Pharmacokinetic study after single oral dose of beta-lactam and fluoroquinolone antimicrobials in Bangladeshi healthy male volunteers (Bangladesh Journal of Physiology and Pharmacology, 2014)
The variability of response to antimicrobial has been inadequately explained because of lack of pharmacokinetic data. The present pharmacokinetic study was designed to provide information beneficial to formulate a population pharmacokinetic model appropriate for Bangladeshi population. Among the beta-lactams, amoxicillin (500 mg), flucloxacillin (250 mg), cefuroxime (500 mg) and among the fluoroquinolones, ciprofloxacin (500 mg), levofloxacin (500 mg), gatifloxacin (400 mg) were studied in 15 healthy Bangladeshi male volunteers. The Cmax, AUC0infinity, Tmax, T1/2 and Ctrough were studied with all antimicrobials. Later, the Cmax and AUC0infinity were adjusted for bodyweight and dose. Among the studied antimicrobials, the Cmax varied to great extent even after adjustment for bodyweight and dose. The Cmax after adjustment was highest in case of flucloxacillin and lowest in case of ciprofloxacin, indicating excellent absorption of flucloxacillin in Bangladeshi population. The information obtained through this study generates necessity of new cut-off value for the antimicrobials.DOI: http://dx.doi.org/10.3329/bjpp.v30i1.20789 Bangladesh J Physiol Pharmacol 2014; 30(1):16-24